ANALISIS PEMAHAMAN LINTAS BUDAYA DALAM PEMBELAJARAN BAHASA JEPANG PADA BUKU TEKS PEMBELAJARAN MARUGOTO A1: AKTIVITAS - Mashfufah, Ulfah; Aibonotika, Arza; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The purpose of this research is to describe how cross cultural understanding concept based of JF Standard on Japanese text book Marugoto A1: Activity and how to apply it in class activity. This research is a qualitative descriptive study with qualitative content analysis as method. The main data source is the textbook of Marugoto A1: Activity. The analysis was done by analyzing the teaching material using interactive data analysis technique. The analysis result show that activities containing the concept of cross-cultural understanding based on JF Standards is Japanese culture are presented in learning materials while other cultures are presented in class activities where students are asked to related Japanese Culture that they have learned and understood with students cultures. Marugoto also prioritizes receptive, productive and interactive systems in learning Japanese Language based on JF Standard through Can-do points that must be achieved in class activities.Key Words: Textbook Analysis; JF Standard; Cross-cultural Understanding